2006
DOI: 10.1016/j.bbadis.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Antigen presenting cells (APCs) from thermally injured and/or septic rats modulate CD4+ T cell responses of naive rat

Abstract: Regulation of immune response is marked by complex interactions among the cells that recognize and present antigens. Antigen presenting cells (APCs), the antigen presenting cell component of the innate immune response plays an important role in effector CD4+ T cell response. Thermal injury and/or superimposed sepsis in rats' leads to suppressed CD4+ T cell functions. We investigated modulations of CD4+ T cell function by APCs (purified non-T cells) from thermally injured and/or septic rats. Rats were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Furthermore, these findings of altered mediator release are underpinned by observations that septic mouse macrophages appear to be differentially utilizing/ activating various signaling pathways (21,23,24,41,52,53) and the upregulation/expression of inhibitory receptors like programmed cell death receptor-1 (PD-1), CD40, etc. (22,25,30,54). Also, while the loss of immune cells via apoptosis is evident in these animals (28,46,59), this is likely, at least in part, a response to the actions of immunesuppressive cell populations or the anti-inflammatory mediators they release (3,40,58).…”
mentioning
confidence: 89%
“…Furthermore, these findings of altered mediator release are underpinned by observations that septic mouse macrophages appear to be differentially utilizing/ activating various signaling pathways (21,23,24,41,52,53) and the upregulation/expression of inhibitory receptors like programmed cell death receptor-1 (PD-1), CD40, etc. (22,25,30,54). Also, while the loss of immune cells via apoptosis is evident in these animals (28,46,59), this is likely, at least in part, a response to the actions of immunesuppressive cell populations or the anti-inflammatory mediators they release (3,40,58).…”
mentioning
confidence: 89%
“…Our present studies have assessed both the individual effects of TI and sepsis as well as an effect of superimposition of sepsis on TI, in rats, on apoptotic responses of MLN CD4 + T cells. While TI or sepsis individually produced low animal mortality, the combined injury resulted in exacerbation of both morbidity and mortality 17,19. Thus, the focus in this study on the combined TI-plus-sepsis injury affords us an opportunity to assess potential non-lethal versus lethal implications of the T cell dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…A number of laboratory and clinical studies have shown that extensive thermal injury induces a state of immune-insufficiency, and that the immune-refractoriness predisposes the injured host to critical morbidity and mortality 7 , 9 , 12 - 16 . To date, their involvement as critical regulatory molecules responsible for T cell suppression in TI and septic injuries continues to be a subject of extensive studies as evident from reports from several laboratories 17 - 20 . The principal outcome of such immune suppression is increased susceptibility of injured host to opportunistic pathogens causing high risk of death.…”
Section: Introductionmentioning
confidence: 99%
“…All animal housing, experimentation and treatment were based on previously published protocols approved by the Chicago State University Animal Care and Use Committee (IACUC) and in accordance with NIH guidelines 1-3. All rats (1) were acclimatized in the animal facility for at least one week before being subjected to any treatment; (2) were given free access to water and standard lab rat chow ad libitum and kept in a 12:12 light-dark from time of arrival till sacrifice; and (3) unless otherwise noted, all treatments including major thermal injury (TI) were carried out between zeitgeber time (ZT) 6 and 8, where ZT 0 represents the onset of the light period of the L-D cycle at 6 a.m. Major thermal injury protocols were previously described and shown to be associated with full thickness 3rd degree skin burns over ~30% of the total body surface associated with fairly consistent inflammation-linked immune as well as gut barrier abnormalities 1-3. Accordingly, upon verification of deep anesthesia with sodium pentobarbital (40-50 mg/kg intraperitoneal, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…These observations point to a great therapeutic potential, especially in relation to gut barrier inflammatory abnormalities associated with major thermal injury and postburn intestinal sepsis pathogenesis 1-3. Here, we begin to closely explore this potential by examining melatonin's postburn gut pathophysiological dynamics.…”
Section: Introductionmentioning
confidence: 99%